Major Issues in Female Dormitories of Universities and their Relationship with Mental Health - YÜKSEL, MÜGE (DEOMED PUBL, ISTANBUL, 2021)
Screening and identifying the problems faced by university students, and finding the sources and understanding the variables that cause these problems are very important for mental health. Campus is an environment that is open to many risk factors and much research has confirmed that university study is particularly difficult for women. The aim of this study is to investigate the problems of female students living in university dormitories in a comprehensive manner and to make a relational analysis in the areas that are considered to be related to these problems. In addition, it aims at determining the extent to which university students' depression, anxiety, stress and psychological wellbeing are predicted by the various problem areas experienced by the students. 122 Female students participated in the study. Newly-Developed Problem Screening Inventory, Depression-Anxiety-Stress Scale (DASS-21) and the Psychological Well-being Scale were used for the data collection. The collected data were analyzed through stepwise regression analysis, which led to the conclusion that personal perception and affective problems are significant predictors for all three variables, drawing attention to the importance of the problems experienced by female students. The findings are discussed in the context of national and international studies on women living in university dormitories, and suggestions and limitations are presented.
Keywords: Anxiety; depression; dormitory; problem screening; psychological support; psychological well-being; stress; student residence; university student; PSYCHOLOGICAL DISTRESS; STUDENTS; PREDICTORS; STRESS; ADAPTATION; PREVALENCE